PENGARUH PENERAPAN MODEL PROBLEM BASED LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS VIII SMPN 43 PADANG - Afifah, Nabila Nur (Jurnal Edukasi dan Penelitian Matematika, 2024)
This research uses PBL model to analyze whether the problem solving ability in class VIII SMPN 43 Padang is better than conventional learning. This research applies a mixture of descriptive and quasy experiment. Data analysis techniques with t-test, where the data requirements must be normally distributed and homogeneous variance. The findings showed that the average quiz score at each meeting always increased and the score for each indicator increased at each meeting. Each increase that occurs shows that the ability under study is getting better, meaning that there is a development of ability during the application of the PBL model. Furthermore, the results also showed that the group with the PBL model was better than the group given the conventional method.Keywords– Mathematical Problem Solving Ability, Conventional Learning, Problem Based Learning